Functional Feeding Group Composition of Macroinvertebrates as Indicators of Ecosystem Health in Jeddo River, Nigeria - Anigboro, Doris O.; Ikomi, Robert Bemigho; Nwaiku, Fidelis (FUDMA Journal of Sciences, 2026)
This study assessed the functional feeding group (FFG) composition of Macroinvertebrates in the Jeddo River, Niger Delta, Nigeria, to evaluate their potential as indicators of ecosystem health. Macroinvertebrate samples were collected from three stations along the river using kick sampling and Ekman grab methods and were identified to genus or species level before being classified into functional feeding groups. Physico-chemical parameters, including temperature, pH, dissolved oxygen, nutrients, and salinity, were measured concurrently to assess environmental conditions. Results revealed that predators dominated the macroinvertebrate community, followed by collector-gatherers and grazers, with notable spatial variation across stations. High predator-to-prey ratios and low representation of sensitive functional groups in certain stations indicated ecological stress and potential habitat degradation. The study highlights that FFG analysis, combined with water quality assessments, provides a robust tool for monitoring river health and detecting early signs of environmental disturbance in tropical estuarine systems. These findings provide baseline information essential for sustainable management and conservation of the Jeddo River and similar aquatic ecosystems in the Niger Delta region.
Keywords: Macroinvertebrates; Functional feeding groups; River health; Niger Delta; Ecosystem monitoring; Estuarine ecology; Anthropogenic impacts